Bare soil hydrological balance model "MHYSAN": Calibration and validation using SAR moisture products and continuous thetaprobe network measurements over bare agricultural soils (Tunisia). (April 2017) - Gorrab, Azza; Simonneaux, Vincent; Zribi, Mehrez; Saadi, Sameh; Baghdadi, Nicolas; Lili Chabaane, Zohra; Fanise, Pascal
Abstract: The present study highlights the potential of multi-temporal X-band Synthetic Aperture Radar (SAR) moisture products to be used for the calibration of a model reproducing soil moisture (SM) variations. We propose the MHYSAN model (Modèle de bilan HYdrique des Sols Agricoles Nus) for simulating soil water balance of bare soils. This model was used to simulate surface evaporation fluxes and SM content at daily time scale over a semi-arid, bare agricultural site in Tunisia (North Africa). Two main approaches are considered in this study. Firstly, the MHYSAN model was successfully calibrated for seven sites using continuous thetaprobe measurements at two depths. Then the possibility to extrapolate local SM simulations at distant sites, based on soil texture similarity only, was tested. This extrapolation was assessed using SAR estimates and manual thetaprobe measurements of SM recorded at these distant sites. The results reveal a bias of approximately 0.63% and 3.04%, and an RMSE equal to 6.11% and 4.5%, for the SAR volumetric SM and manual thetaprobe measurements, respectively. In a second approach, the MHYSAN model was calibrated using seven very high-resolution SAR (TerraSAR-X) SM outputs ranging over only two months. The simulated SM were validated using continuous thetaprobe measurements during 15 months. Although the SM was measured on only seven different dates for the purposes of calibration, satisfactory results were obtained as a result of the wide range of SM values recorded in these seven images. This led to good overall calibration of the soil parameters, thus demonstrating the considerable potential of Sentinel-1 images for daily soil moisture monitoring using simple models. Graphical abstract: Highlights: A simple two layer soil model reproduces well the moisture dynamics of bare soils at daily time step. We analyze the feasibility of spatial extrapolation of soil moisture based on texture properties. SAR image estimates of soil moisture for seven dates with contrasted moisture are successfully used to calibrate the model.